Comparison of in Vitro Bioactivation of Flutamide and Its Cyano Analogue: Evidence for Reductive Activation by Human NADPH:Cytochrome P450 Reductase - Wen, Bo (2008)
Flutamide (FLU), a nonsteroidal antiandrogen drug widely used in the treatment of prostate cancer, has been associated with idiosyncratic hepatotoxicity in patients. It is proposed that bioactivation of FLU and subsequent binding of reactive metabolite(s) to cellular proteins play a causative role. A toxicogenomic study comparing FLU and its nitro to cyano analogue (CYA) showed that the nitroaromatic group of FLU enhanced cytotoxicity to hepatocytes, indicating that reduction of the nitroaromatic group may represent a potential route of FLU-induced hepatotoxicity [Coe et al. (2007) Chem. Res. Toxicol. 20, 1277–1290]. In the current study, we compared in vitro bioactivation of FLU and CYA in human liver microsomes and cryopreserved human hepatocytes. A nitroreduction metabolite FLU-6 was formed in liver microsomal incubations of FLU under atmospheric oxygen levels and, to a greater extent, under anaerobic conditions. Seven glutathione (GSH) adducts of FLU, FLU-G1–7, were tentatively identified in human liver microsomal incubations using liquid chromatography–tandem mass spectrometry (LC/MS/MS), while CYA formed only four corresponding GSH adducts, CYA-G1–4, under the same conditions. Of particular interest was the formation of FLU-G5–7 from FLU, where the nitroaromatic group of FLU was reduced to an amino group. A tentative pathway is that upon nitroreduction, the para-diamines undergo cytochrome P450 (P450)-catalyzed two-electron oxidations to form corresponding para-diimine intermediates that react with GSH to form GSH adducts FLU-G5–7, respectively. The identities of FLU-G5–7 were further confirmed by LC/MS/MS analyses of microsomal incubations of a synthesized standard FLU-6. In an attempt to identify enzymes involved in the nitroreduction of FLU, NADPH:cytochrome P450 reductase (CPR) was shown to reduce FLU to FLU-6 under both aerobic and anaerobic conditions. Furthermore, the formation of FLU-G5–7 was completely blocked by the addition of a reversible CPR inhibitor, α-lipoic acid, to the incubations of FLU under aerobic conditions. In summary, these results clearly demonstrate that nitroreduction of FLU by CPR contributes to bioactivation and potentially to hepatotoxicity of FLU.